The end of the world as we know it : public ethics in times of de-standardization and individualization - Demmke, Christoph; Autioniemi, Jari; Lenner, Florian (Taylor & Francis, 2021)
Current governance and managerial trends emphasize context-oriented and best-fit approaches, de-standardization and the role of individual discretion in decision-making. We discuss the results of a European-wide study on the effectiveness of Conflict of Interest (CoI) policies for Ministers in a de-standardized context. Our results show trends towards individualized and sophisticated policies and approaches in the field of CoI. Policies are also becoming more bureaucratic and complex. The implementation of these policies tends to suffer from shortcomings. These shortcomings generate doubts as to whether ethics policies have become more effective.
Keywords: Governance; Good Governance; Public Management Reform; Moral Relativism; ethics; fi=Julkisjohtaminen|en=Public Management|